Analysis of spatial and temporal variations in bacterial community dynamics within stream biofilms. Issue 4 (2nd October 2021) - Gautam, Anju; Lear, Gavin; Lewis, Gillian D.
ABSTRACT: Stream biofilms play an important ecological role in the supply of energy and organic matter to aquatic food webs. Bacterial community composition in stream biofilms is shaped by biotic interactions as well as physicochemical conditions which vary across space and time. However, knowledge of the relative importance of spatial versus temporal factors for microbial community composition is lacking. Here, we applied 16S rRNA gene sequencing to characterise the biofilm bacterial community composition of 732 stream biofilms. These biofilm samples were collected within six streams located a maximum of 118 km apart and draining different catchment types (forest, urban and rural land uses). Samples were collected at monthly intervals for 30 months over 2013–2015. Bacterial community composition was explained better by monthly changes (PERMANOVA; p < 0.01) than by differences observed among streams and catchment types (PERMANOVA; p = 0.44). Bacterial community composition over months and years followed a discernible cyclical seasonal pattern, as quantified using periodic regression analysis. Temperature, TN, light, and soil moisture deficit were identified as factors most significantly correlated with seasonal variation in bacterial community composition. Overall, these findings suggest that temporal changes are more important than spatial changes across the scales investigated in this study.